2013
DOI: 10.1074/jbc.m112.419713
|View full text |Cite
|
Sign up to set email alerts
|

A Truncated Fragment of Src Protein Kinase Generated by Calpain-mediated Cleavage Is a Mediator of Neuronal Death in Excitotoxicity

Abstract: Background: Abnormal regulation of calpains and Src contributes to stroke-induced brain damage. Results:The abnormally activated calpains cleave Src to generate a truncated Src fragment capable of directing neurons to undergo cell death. Conclusion:A new function of Src in neuronal death is discovered. Significance: Prevention of calpain-mediated cleavage of Src is a potential therapeutic strategy to minimize stroke-induced brain damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(99 citation statements)
references
References 57 publications
10
89
0
Order By: Relevance
“…Although Src plays an important role in GDNF-induced neuronal survival (Encinas et al, 2004) and its knock-down or chemical inhibition induces neuronal death (Iqbal Hossain et al, 2015), Src inhibitors have been shown to be neuroprotective in transient and permanent models of brain ischemia (Liang et al, 2009). This antithetic role of Src can be explained considering the effects of excitotoxicity-and ischemiainduced calpain-mediated truncation of Src (Hossain et al, 2013).…”
Section: Calpain-mediated Cleavage Of Nmdar-associated Kinasesmentioning
confidence: 97%
See 1 more Smart Citation
“…Although Src plays an important role in GDNF-induced neuronal survival (Encinas et al, 2004) and its knock-down or chemical inhibition induces neuronal death (Iqbal Hossain et al, 2015), Src inhibitors have been shown to be neuroprotective in transient and permanent models of brain ischemia (Liang et al, 2009). This antithetic role of Src can be explained considering the effects of excitotoxicity-and ischemiainduced calpain-mediated truncation of Src (Hossain et al, 2013).…”
Section: Calpain-mediated Cleavage Of Nmdar-associated Kinasesmentioning
confidence: 97%
“…Similar results were obtained in vivo, in the endothelin-1 model of stroke in rats. In vitro experiments, with recombinant calpains and mass spectrometry analysis, showed that Src is cleaved in the segment between residues 63 and 78 of the unique domain at the N-terminus, generating a 52 kDa fragment lacking the myristoyl group attached at the N-terminus, that still retains kinase activity (Hossain et al, 2013). In vitro studies using synaptic membranes showed that Src-mediated phosphorylation of GluN2A and GluN2B reduces calpain-mediated truncation, but has no effect on GluA1 truncation (Rong et al, 2001) (see section 5.1.8).…”
Section: Calpain-mediated Cleavage Of Nmdar-associated Kinasesmentioning
confidence: 98%
“…In this study, co-immunoprecipitation was used to study the relationship of PTPN13 and Src, and it was found that Src can bind with PTPN13 in H520 cells (Figure 4A). All members of Src kinase family have a catalytic domain preceded by two Src-homology domains (SH2 and SH3), including proto-oncogene tyrosine-protein kinase (NP_114183.1, ~542 aa) [22, 39]. SH2 and SH3 modules cooperate in regulating the phosphorylation activity of Src kinases [27, 40].…”
Section: Resultsmentioning
confidence: 99%
“…***, p Ͻ 0.001; *, p Ͻ 0.05. via phosphorylation of critical factors and enzymes (46). More recently, it has been demonstrated that calpain-mediated generation of toxic fragments affects neuronal survival during glutamate receptor-mediated excitotoxicity (47). Therefore, understanding of how calpain-mediated cleavage of critical substrates is regulated is considered important for blocking dis- ؉ -stereotaxic injection model.…”
Section: Discussionmentioning
confidence: 99%